Changes in body composition and aerobic capacity of football players during the half season of Bosnia and Herzegovina Premier league - Colakhodzic, E.; Baltic, AQ.; Suta, D. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The goal of the research was to determine changes in body composition and aerobic capacity of senior football players generated in semi-annual cycle of Bosnia and Herzegovina`s Premiership League. Regarding the time aspect, this research has a longitudinal character aiming to determine changes in body composition and aerobic capacity on the sample of 23 senior football players (25.45 ±5.74 years of age; 182.9 ±5.94 cm height; 76.9 ±6.39 kg weight) of the F.C. Velež, Mostar, that originated between two points in time. Body composition is determined by BIA method (Bioelectrical Impedance Analysis), using the electronicscales TANITA TBF- 300 (Tanita corporation of America Inc.), while the aerobic capacity was determined indirectly by BEEP test. Measurements were made at the beginning of the preparation period of the 2013/14 spring half season of Bosnia and Herzegovina`s Premiership League and seven days after the official end of the half season. The changes induced by controlled programmed activities have made, in terms of statistics, significant impact on the fat tissue quantity in kilograms (FATMAS t=3.44; sig.= .002), fat tissue percentage (FAT% t=3.84; sig.= .001) and tissue impedance (IMPEDANCE t=3.44; sig.= .002) of the football players at the statistic relevancy p=.05. There were no statistically significant changes regarding other body composition variables, or the value of aerobic capacity in L/kg/min-1 (VO2MAX t=1.234; sig.= .230). It is evident that the football half season which includes 45 days preparation period and 15 games during the League competition has not induced statistically significant changes in height, mass, accumulated energy, muscular mass quantity and fluids quantity in the body. The changes were statistically insignificant in the aerobic capacity as well. After the winter break, which is very long in the Bosnia and Herzegovina`s Premiership League, lasting approximately two months, the training program of the team in the preparation period was focused on the reduction of the fat tissue and achieving and maintaining a certain level of aerobic capacities - conditional readiness of the team.